The McDonaldization of CAEP accreditation and teacher education programs abroad. (April 2020) - Romanowski, Michael H.; Alkhateeb, Hadeel
Abstract: McDonaldization is the processes of the fast-food industry that dominate segments of societies worldwide. Few studies address how McDonaldization applies to the accreditation of teacher education programs. This article demonstrates how the Council for the Accreditation of Education Programs (CAEP) could be perceived as a McDonaldized organization that propagates American understandings of teacher education in non-US universities. The article applies the five principles of McDonaldization to CAEP Accreditation and addresses possible influences on non-US universities seeking CAEP accreditation outside the US borders. Specifically, the article discusses the cultural challenges, language concerns, and issues regarding indigenous knowledge that non-US universities face. Highlights: CAEP Accreditation could be perceived as a McDonaldized organization. McDonaldization's five principles are evident CAEP Accreditation. CAEP Accreditation propagates American understandings of teacher education in non-US universities. Accreditation presents non-US universities with challenges in cultural, language and indigenous knowledge.